Pedagogia hospitalar no Brasil: revisão integrativa da produção do conhecimento no Estado de Roraima frente ao cenário nacional no período de 2011 até 2020 - Almeida, Paola Beatriz Frota (2022)
This research aimed to understanding the current state of the insertion of Hospital Pedagogy into Roraima facing the national scenario, based on integrative systematic review of literature from 2011 to 2020. The Hospital Pedagogy refers a multidisciplinary educational action that offers to the child and youngster into hospital and residence environments; a school, emotional and social supports, guided by theories and practices based on science and human dignity. One of these concepts is the theme "social inclusion", establishing a link with the proposal of Line 2, "Education and Inclusive Processes, of the Master's in Education", offered by the Graduate Program in Education at the Federal University of Roraima, with enrichings academics discussions, considering complex the aspect inherent to the subjects and contexts that emerge from society. The methodology followed the steps for a systematic-integrative literature review. The searches for knowledge productions in the national scenario were based on the scientific data platforms, which by means of the key words "hospital pedagogy and education; hospital class and education and hospital pedagogy and hospital class and education, added to the filters and inclusion criteria, it was reached a sample of 12 articles, 41 dissertations and 8 thesis, totalizing in 61 productions. The methodology applied for the search in the State of Roraima was the access to the digital libraries of the Federal University of Roraima, State University of Roraima and Federal Institute of Roraima. The systematic review was applied in each scenario, with the objective of contextualizing the scenarios and profiling the productions found. The results of the systematic review pointed out that Northern's Brazil region produced the least, while the Southeastern's Brazil region produced the most; the state of Sao Paulo was the most that published articles, and the area of Education was the most expressive in this results. The qualitative analysis was done under the categories "Teacher Training", "Pedagogical Practices" and "Hospital Pedagogy - implementation and structure", defined from the thematic focuses most addressed in the researches and for considering relevant to know the main notes, challenges and directions from these analysis categories. The results highlighted in both scenarios point to certain similarities. About the Teacher Training category, the need for discussion about the curricular guidelines in initial training was highlighted, with the inclusion of Special Education content, and the need to establish partnerships with the public sector to intervene in continuing education. As for the Pedagogical Practices category, despite the importance given to the presence of the teacher in the hospital, difficulties in planning for a public of different ages, scarces materials resources, appreciation and communication with the health team and school teachers were highlighted. About the implantation and structure of Hospital Pedagogy, the studies often report an inappropriate physical structure, lack of specific regulation of Hospital Pedagogy or home care by the County or States, and the need to expand researches as a way to divulge and strengthen Hospital Pedagogy in Brazil. As a way to continuously advance in the Hospital Pedagogy area, this study is a step, a stage in this incessant journey towards the achievement of strategies to offer inclusive practices through education in the hospital environment.